2023
DOI: 10.1021/acs.biochem.3c00425
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the Alzheimer’s Disease Tau Core Structure from Recombinant Tau297–391 Yields Variable Quaternary Structures as Seen by Negative Stain and Cryo-EM

Calina Glynn,
Joshua E. Chun,
Cameron C. Donahue
et al.

Abstract: The protein tau misfolds into disease-specific fibrillar structures in more than 20 neurodegenerative diseases collectively referred to as tauopathies. To understand and prevent disease-specific mechanisms of filament formation, in vitro models for aggregation that robustly yield these different end point structures will be necessary. Here, we used cryo-electron microscopy (cryo-EM) to reconstruct fibril polymorphs taken on by residues 297−391 of tau under conditions previously shown to give rise to the core s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We hypothesized that AD-specific PTMs can facilitate the nucleation of Tau paired helical filaments in vitro . The Tau region of interest was selected based on the published study that identified Tau(297-391) as the sequence that recapitulates the AD fold in vitro, 1317 and our prior synthetic work which indicated a strategically advantageous synthetic disconnection at C291 to produce a peptide fragment Tau(291-391). 45 We selected three PTMs that are linked to Tau physiology and disfunction: Acetylation of Tau filaments occurs in the region that forms the rigid fibril core and usually overlaps with ubiquitination sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that AD-specific PTMs can facilitate the nucleation of Tau paired helical filaments in vitro . The Tau region of interest was selected based on the published study that identified Tau(297-391) as the sequence that recapitulates the AD fold in vitro, 1317 and our prior synthetic work which indicated a strategically advantageous synthetic disconnection at C291 to produce a peptide fragment Tau(291-391). 45 We selected three PTMs that are linked to Tau physiology and disfunction: Acetylation of Tau filaments occurs in the region that forms the rigid fibril core and usually overlaps with ubiquitination sites.…”
Section: Resultsmentioning
confidence: 99%
“…1012 Only recently aided by high-throughput cryo-EM, short fragments of Tau have been shown to self-assemble into the AD and CTE filaments, but these peptides also form many other structures under similar conditions (Figure 1). 1317…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation